Effect of particle size on dry sliding wear behaviour of sillimanite reinforced aluminium matrix composites. Issue 1 (January 2018) - Sharma, Sandeep; Nanda, Tarun; Pandey, O.P.
Abstract: Present work describes the development of Al-Si/sillimanite reinforced composites via stir casting route. Sillimanite is abundant mineral available in coastal regions of India and has not been explored much as reinforced mineral for the development of composites. In the present work, dry sliding wear behaviour of LM30 aluminium alloy reinforced with sillimanite has been investigated. Composites reinforced with sillimanite in different weight percentage (3–18 wt percentage) and particle size range (fine: 1–20 µm, medium: 32–50 µm, and coarse: 75–106 µm) were prepared. Microstructural studies revealed uniform distribution of sillimanite particles in the matrix of composites. Nanoindentation taken at different phases indicated good bonding between reinforced particles and matrix. Fine particles (1–20 µm) reinforced composites containing 15 wt% sillimanite exhibited higher wear resistance which is 55% more compared to base LM30 alloy. Beyond this reinforcement level, wear resistance deteriorated because of agglomeration of the fine particles. Analysis of wear track and debris revealed that at low applied loads, abrasive wear was predominant whereas at higher applied loads, adhesive wear was dominating factor.